2023
DOI: 10.1002/ange.202218174
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Carrier Diffusion Enables Efficient Back‐Contact Perovskite Photovoltaics

Abstract: Back‐contact architectures offer a promising route to improve the record efficiencies of perovskite solar cells (PSCs) by eliminating parasitic light absorption. However, the performance of back‐contact PSCs is limited by inadequate carrier diffusion in perovskite. Here, we report that perovskite films with a preferred out‐of‐plane orientation show improved carrier dynamic properties. With the addition of guanidine thiocyanate, the films exhibit carrier lifetimes and mobilities increased by 3–5 times, leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…While the SPO PCEs for both types of devices were similar, the integrated J sc of ordered-perovskite devices was slightly higher, reinforcing the positive impact of crystal orientation (Figure i,j). Currently, there is a widespread discussion on improving the performance of perovskite macroscopic devices through microcrystal orientation. Our experiments have shown that there is a strong anticorrelation between current and external bias in random-perovskite films at the microscopic level. However, the ordered-perovskite films exhibit significant improvements in current homogeneity and optoelectronic properties.…”
Section: Resultsmentioning
confidence: 78%
“…While the SPO PCEs for both types of devices were similar, the integrated J sc of ordered-perovskite devices was slightly higher, reinforcing the positive impact of crystal orientation (Figure i,j). Currently, there is a widespread discussion on improving the performance of perovskite macroscopic devices through microcrystal orientation. Our experiments have shown that there is a strong anticorrelation between current and external bias in random-perovskite films at the microscopic level. However, the ordered-perovskite films exhibit significant improvements in current homogeneity and optoelectronic properties.…”
Section: Resultsmentioning
confidence: 78%